Micro-accelerometer Based on Vertically Movable Gate Field Effect Transistor - Kang, Heung Seok; Lee, Kang-Hee; Yang, Dong-Youk; You, Byoung Hee; Song, In-Hyouk (Nano-Micro Letters, 2015)
A vertically movable gate field effect transistor (VMGFET) is proposed and demonstrated for a micro-accelerometer application. The VMGFET using air gap as an insulator layer allows the gate to move on the substrate vertically by external forces. Finite element analysis is used to simulate mechanical behaviors of the designed structure. For the simulation, the ground acceleration spectrum of the 1952 Kern County Earthquake is employed to investigate the structural integrity of the sensor in vibration. Based on the simulation, a prototype VMGFET accelerometer is fabricated from silicon on insulator wafer. According to current–voltage characteristics of the prototype VMGFET, the threshold voltage is measured to be 2.32 V, which determines the effective charge density and the mutual transconductance of 1.545×10−8 C cm−2 and 6.59 mA V−1, respectively. The device sensitivity is 9.36–9.42 mV g−1 in the low frequency, and the first natural frequency is found to be 1230 Hz. The profile smoothness of the sensed signal is in 3 dB range up to 1 kHz.